Persistence of viral RNA segments in the central nervous system of mice after recovery from acute influenza A virus infection - Park, C.H; Matsuda, K; Sunden, Y; Ninomiya, A; Takada, A; Ito, H; Kimura, T; Ochiai, K; Kida, H; Umemura, T (Veterinary Microbiology, 2003)
One-hundred thirty-seven BALB/c mice were intranasally inoculated with neurotropic avian influenza A virus (H5N3). Thirty-nine of these mice died within 16 days post-inoculation (PID) and 98 of the mice recovered from the infection. To investigate whether viral antigens and genomes persist in the central nervous system (CNS) of recovered mice, immunohistochemistry and reverse transcription-polymerase chain reaction (RT-PCR) methods were performed. Histopathologically, mild interstitial pneumonia and non-suppurative encephalomyelitis restricted to the basal part of the frontal lobe of the cerebrum, brain stem and thoracic spinal cord were observed in BALB/c mice until 40 PID. Small amounts of viral antigens were detected in the brain and spinal cord and some viral RNA segments (NA, NP, M, PA, HA, NS, PB1) were intermittently detected in the CNS until 48 PID. Immunosuppression of these mice by dexamethazone (DEX) treatment did not increase the frequency of detection of the lesions, viral antigens or genomes. These findings suggest that viral genomes of neurovirulent influenza virus persist with restricted transcriptive activity in the CNS of the mice even after clinical recovery from the infection.